Pelaksanaan perjanjian pemerintah daerah dan PT. Usaha Nasional Mandiri dalam proyek pembangunan dermaga penyeberangan Tondasi Sulawesi Tenggara - ABUNAWAS, Rezky Olivia Weryana ([Yogyakarta] : Universitas Gadjah Mada, 2009)
This research aims to find out what wanprestasi exist in the implementation of the agreement between Local Government and PT. Business in implementing the National Autonomous Development Project cross-pier in Tondasi Sulawesi. This research is research that is where the judicial data collected in this research include primary data and secondary data obtained from research in the field and literature, primary data obtained through interviews with respondents and secondary data with is getting how to collect data from the literature covering the basics of law, the law systematic, and the rule of law-related problems examined. Overall the data obtained analyzed qualitatively. Based on the results of research found that the existence the wanpresrasi done by the service provider is not implementing the construction work in accordance with the technical specifications and images defined in the contract and misuse of authority, opportunity or means to divert the responsibility of some major work projects to other people or to sub-rent to other parties and the responsibility is to replace the loss pimpro Country / region and imposed administrative sanctions such as dismissal from the department and relegation on the platform at the lower and criminal penalties to prison for 4 (four) years 7 (seven) month, the responsibility of the power of PT.National Independent Business is changing as a result of losses from the excess payment for work project, subject to administrative sanctions such as revocation of business licenses and revocation of permits and construction work to undergo criminal prison sentence for five (5) years.